Evaluating the efficacy and safety of transdermal electrical stimulation on the visual functions of patients with retinitis pigmentosa: a clinical trial protocol for a prospective, multicentre, randomised, double-masked and sham-controlled design (ePICO trial) - Takayuki Baba; Shuichi Yamamoto; Yohei Kawasaki; Tadami Fujiwara; Hideki Hanaoka; Gen Miura; Yoshihito Ozawa; Yuki Shiko; Takayuki Iwase (BMJ Open, 2022)
Introduction Previously, we conducted a clinical trial to evaluate the safety and efficacy of transdermal electrical stimulation (TdES) with skin electrodes to improve the visual functions in patients with retinitis pigmentosa (RP). No adverse events were related to the treatment during follow-up examinations, and TdES significantly improved the mean visual acuity and visual field sensitivity.Methods and analysis We developed a study protocol for a prospective, multicentre, randomised, double-masked and sham-controlled clinical trial, planned to commence on June 2021. We intend to compare the maintenance or improvement in best-corrected visual acuity, and safety of TdES using skin electrodes between patients with RP and the sham group. The primary endpoint comprises the superiority of the logarithm of the minimum angle of resolution (logMAR) visual acuity change at week 24 from baseline in the treatment and sham groups. Secondary endpoints involve the comparison of the treatment and sham groups at week 24 for the logMAR visual acuity, early treatment diabetic retinopathy study visual acuity, the mean deviation value of Humphrey field analyser 10-2, monocular Humphrey Esterman visual field test score, ellipsoid zone length, central foveal thickness and 25-item National Eye Institute Visual Function Questionnaire score. We intend to enrol 50 patients from three Japanese institutions within 1 year and follow them up for 1 years.Ethics and dissemination The protocol was approved by the institutional review board at the Chiba University Hospital and two other institutions, and was registered with the Japan Registry of Clinical Trials on 17 May 2021. The trial will be conducted in accordance with the principles of the Declaration of Helsinki, and is in accordance with Good Clinical Practice standards. The findings will be published in a peer-reviewed journal.Trial registration number JRCT2032210094.